2019
DOI: 10.1093/jnci/djz110
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Cost of Organized Outreach for Colorectal Cancer Screening: A Randomized, Controlled Trial

Abstract: Background Colorectal cancer (CRC) screening remains underused, especially in safety-net systems. The objective of this study was to determine the effectiveness, costs, and cost-effectiveness of organized outreach using fecal immunochemical tests (FITs) compared with usual care. Methods Patients age 50–75 years eligible for CRC screening from eight participating primary care safety-net clinics were randomly assigned to outrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
98
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(105 citation statements)
references
References 32 publications
0
98
0
Order By: Relevance
“…Our prior research demonstrated that the cost to perform outreach for one individual was $23 and the cost per additional patient screened was $112; both acceptable costs on face value given the established benefit of CRC screening. 23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our prior research demonstrated that the cost to perform outreach for one individual was $23 and the cost per additional patient screened was $112; both acceptable costs on face value given the established benefit of CRC screening. 23 …”
Section: Discussionmentioning
confidence: 99%
“…Despite these limitations, mailed outreach remains cost effective even with suboptimal follow-up colonoscopy rates. 23 …”
Section: Discussionmentioning
confidence: 99%
“…A microcosting and long-term modeling study from a San Francisco safetynet health system reported a cost of $23 per patient for outreach delivery and a cost of $112 per patient screened for a program that included an informational postcard, FIT kit, and reminder telephone calls. 65 Another modeling study evaluated the cost-effectiveness of extending a FIT outreach strategy on a national level. 66 The authors reported that this strategy would provide CRC screening to approximately 9.4 million people, preventing 3100 CRC-related deaths, at a cost of $277.9 million.…”
Section: Kq9: What Is the Cost-effectiveness (Cost Per Additional Permentioning
confidence: 99%
“…Electronic medical records and registries can identify patients not up to date with screening, use of at-home FIT kits mailed directly to patients can be expanded, and positive tests can be followed up with automated calls and text prompts from direct patient messaging platforms—all strategies that have proven effective at increasing screening rates and follow-up. Increased utilization of FIT would triage higher-risk patients to colonoscopy, allowing endoscopy units to better manage procedure backlog volume and limit unnecessary patient exposures ( 5 ).…”
mentioning
confidence: 99%